Semiconductors: X‐Ray Writing of Metallic Conductivity and Oxygen Vacancies at Silicon/SrTiO3 Interfaces (Adv. Funct. Mater. 25/2019). (18th June 2019) - Chikina, Alla; Caputo, Marco; Naamneh, Muntaser; Christensen, Dennis Valbjørn; Schmitt, Thorsten; Radovic, Milan; Strocov, Vladimir N.
Abstract : Two‐dimensional electronic states at interfaces are often endowed with novel properties that are promising for future technological applications. Defects at oxide interfaces, in particular, oxygen vacancies play a major role in controlling electronic and magnetic properties at the interfaces. In article number 1900645, Alla Chikina and co‐workers report lithography‐like writing of a metallic state at the interface between SrTiO3 and amorphous Si using X‐ray irradiation.